CBP-dependent memory consolidation in the prefrontal cortex supports object-location learning - Vieira, Philip A. (Hippocampus, 2015)
Recognition of an object's location in space is supported by hippocampus-dependent recollection. Converging evidence strongly suggests that the interplay between the prefrontal cortex and hippocampus is critical for spatial memory. Lesion, pharmacological and genetic studies have been successful in dissecting the role of plasticity in the hippocampal circuit in a variety of neural processes relevant to spatial memory, including memory for the location of objects. However, prefrontal mechanisms underlying spatial memory are less well understood. Here we show that an acute hypofunction of the cyclic-AMP regulatory element binding protein (CREB) Binding Protein (CBP) histone acetyltransferase (HAT) in the medial prefrontal cortex (mPFC) results in delay-dependent disruption of object-location memory. These data suggest that mechanisms involving CBP HAT-mediated lysine acetylation of nuclear proteins support selectively long-term encoding in the mPFC circuits. Evidence from the object-location task suggests that long-term memory encoding within the mPFC complements hippocampus-dependent spatial memory mechanisms and may be critical for broader network integration of information necessary for an assessment of subtle spatial differences to guide appropriate behavioral response during retrieval of spatial memories.